ESTETIKA ORNAMEN MASJID JAMI’ AIR TIRIS KABUPATEN KAMPAR PROVINSI RIAU - Rahmayanis Rahmayanis; Ahmad Akmal; Riswel Zam (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT This writing reveals the aesthetics of ornaments on the Mosque Jami’ located on Pasar Usang, Air Tiris, Kampar district, Riau province. Ornaments found on the mosque inspired by the form of plants, animal, geometry, universe, calligraphy and other forms. The forms of plant are keluk pakis (fern branch), pucuk rebung (baby bamboo) and tampuk manggis (mangosteen calyx); the motif of animal is lebah bergayut (swaying bee); and the motifs of universe are spirals, cloud, moon and star. Ornaments are applied on the wall, roof, pole, podium, tower and list-plank. Mosques ornaments have meaning and function as building decoration and symbolizing the unity of Air Tiris people. The contents of form and meaning in their application are related to the function of mosque namely as the place for conducting religious activities and democratic discussions. The application of carving ornament forms based on the cultural and aesthetic studies is related to meaning and philosophy that refer to noble values in people’s life namely customary and religious values. This research used qualitative method that had descriptive characteristic, and use cultural approach as the basis of analysis. Data were collected through observation done to the forms of contents of ornaments possessing the identity of Mosque Jami’ and through interview done with interviewees. Analysis was conducted by formulating the content, form and meaning of ornaments on Mosque Jami’ with the help of cultural theory and aesthetic theory in order to perform interpretation that resulted on the conclusion. Keywords: Aesthetics, Ornaments, Mosque Jami’, Air Tiris